Basel III Impact on Czech Banks and Effectivity of Capital Ratios to Predict Bank Distress - Matejašák, Milan (2015)
The aim of this thesis is to evaluate the impact of Basel III on Czech banks and to compare the effectiveness of capital ratios in predicting bank distress. After a short introduction, in the second chapter we estimate the impact of tightened Basel III capital regulation on lending spreads in the Czech banking sector. In this chapter we conclude that the tightened capital regulation will not lead to more expensive borrowing in the Czech Republic mainly because the banking sector has been well-capitalized. In the third chapter we identify the strategies that Czech banks adopted in order to significantly increase their capital ratios between 2009 and 2013. Our analysis shows that retained earnings have played a major role in increasing the average capital adequacy of Czech banks. In addition, the Czech banks have decreased their average asset risk to further strengthen the overall capital adequacy ratio. In the last chapter, using a dataset on bank distress in European banks during 2008-2012, we compare the performance of risk-weighted capital ratios and simple leverage capital ratios to predict bank distress. Our results suggest that simple leverage ratios can perform better than complex risk-weighted capital ratios when predicting bank distress. While such a finding is not conclusive, it suggests that more complex risk modeling does not always mean better risk modeling.